César Aira, Alejandra Pizarnik. Rosario, Beatriz Viterbo Editora, 1998, 71 págs. - Straccali, María Eugenia (1998)
Fil: Straccali, María Eugenia. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.